2020 Computing in Cardiology Conference (CinC) 2020
DOI: 10.22489/cinc.2020.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthesia on Fetal-Maternal Heart Rate Variability and Coupling in Pregnant Mice and Fetuses

Abstract: To evaluate and assess the cardiovascular system during fetal development in the utero of pregnant mouse, it is essential to understand the effect of mandatory anesthesia treatment on sympathetic and parasympathetic nervous system activities. The preliminary study presented in this paper explores the changes in fetal and maternal Heart Rate Variability (HRV) parameters as well as fetalmaternal Heart Rate (HR) coupling measures during anesthesia. ECG signals of 6 pregnant mice and 10 fetuses were recorded for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…An additional six studies were found through other resources; three were found by searching the references of studies included through the database search, while three were found via searches of publications from researchers active in the field of MFCC. The latter three were either conference papers from technically oriented conference proceedings [ 24 ] or articles from journals that are not listed in PubMed, Embase, or Cochrane [ 8 , 12 ]. After removing the duplicate studies, 4,813 unique studies remained, of which 32 were found eligible for full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…An additional six studies were found through other resources; three were found by searching the references of studies included through the database search, while three were found via searches of publications from researchers active in the field of MFCC. The latter three were either conference papers from technically oriented conference proceedings [ 24 ] or articles from journals that are not listed in PubMed, Embase, or Cochrane [ 8 , 12 ]. After removing the duplicate studies, 4,813 unique studies remained, of which 32 were found eligible for full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…has attracted our interest. We have reported in our previous studies (Khandoker et al, 2016;Khandoker et al, 2017;Khandoker et al, 2018;Khandoker et al, 2020) that pregnant mice models pave the way for a better understanding of the embryonic nervous system development. A single mouse embryo cell requires three weeks to become a fully-grown newborn (Kaufman, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The intuitive question “How can research findings in mice models be extrapolated to human physiology?” has attracted our interest. We have reported in our previous studies ( Khandoker et al, 2016 , 2017 , 2018 , 2020 ) that pregnant mice models pave the way for a better understanding of the embryonic nervous system development. A single mouse embryo cell requires 3 weeks to become a fully-grown newborn ( Kaufman, 1992 ).…”
Section: Introductionmentioning
confidence: 99%